Monitoring practices in Brazilian credit unions: a study on monitoring and accounting indicators - Zanetti Trindade, Luana; Bialoskorski Neto, Sigismundo (REBRAE, 2016)
Monitoring helps in incentive mechanisms and punishment because it allows us to observe the behavior and give credibility to the system because the agent understands that monitoring is to redevelop or punish their attitudes. It requires the development of a monitoring framework that recognizes the existence of heterogeneity of members and that allows the survival of the cooperative organization. In addition, a monitoring economic results and to provide services and control by multiple principals who are cooperative members is necessary. Therefore, monitoring reduces moral hazard and thus increases the efficiency of the organization. It is critical to monitor the economic results and to provide services and control by multiple principals who are members of the cooperative. This therefore cooperatives have economic objectives for the provision of services to their members. The research question is: higher compliance monitoring practices indicated by the Central Bank (BACEN) influences the financial statements as assets, revenues and surplus? Thus, the aim of this work is to identify if certain accounting information is influenced by greater adherence to monitoring practices. This research aims to contribute to the understanding of the relationship between monitoring practices, which possibly implies the reduction of agency costs and consequently the efficiency of cooperative organizations, and accounting information as an asset, revenue and surplus. After the analysis of the mean difference test, we can see that the higher compliance monitoring practices indicated by the Central Bank can influence a higher asset value, higher value of revenue and a higher surplus in credit unions. Not being able to infer that a greater adherence monitoring practices directly influence asset, revenue and surplus or those variables that influence higher compliance monitoring practices have become a problem of endogeneity. Can only infer that there is an influence between greater adherence practices and monitoring these variables.